Building Metacognitive Skills Using AI Tools to Help Higher Education Students Reflect on Their Learning Process - Nacereddine Mazari (RHS Revista Humanismo y Sociedad)
This study examines how AI can be used to improve higher education students’ ability to learn effectively. The research focuses on using AI to enhance metacognition, which is the students’ ability to understand and control their learning processes. Specifically, the study explores the potential of AI-powered prompts to encourage individuals to reflect on their learning and explain their understanding of the materials provided by teachers. Additionally, it highlights the benefits of implementing AI-powered learning companions to provide personalized support and guidance throughout the learning process. Recommendations for future research include investigating how AI can further improve students’ self-regulation skills and enhance peer-review processes through AI-generated feedback.